2023
DOI: 10.1093/eurheartj/ehac779.104
|View full text |Cite
|
Sign up to set email alerts
|

Association between non-alcoholic fatty liver disease and incidence of arrhythmia and other cardiovascular outcomes: a systematic review and meta-analysis

Abstract: Funding Acknowledgements Type of funding sources: None. Background The association between non-alcoholic fatty liver disease (NAFLD) with cardiovascular and cerebrovascular outcomes, as well as their clinical impact, has yet to be established in the literature. Objective We aim to evaluate the association between NAFLD patients and the risk of atrial fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This meta‐analysis was conducted and reported following the Cochrane and PRISMA (Preferred Reporting Items for Systematic Review and Meta‐analysis) 2020 guidelines and performed according to established methods, as described previously 15–17 . The pre‐specified study protocol has been registered in the PROSPERO (CRD42023424652).…”
Section: Methodsmentioning
confidence: 99%
“…This meta‐analysis was conducted and reported following the Cochrane and PRISMA (Preferred Reporting Items for Systematic Review and Meta‐analysis) 2020 guidelines and performed according to established methods, as described previously 15–17 . The pre‐specified study protocol has been registered in the PROSPERO (CRD42023424652).…”
Section: Methodsmentioning
confidence: 99%
“…Cancer and heart failure (HF) are two major causes of morbidity and mortality with a complex inter‐relationship including shared risk factors and overlapping pathophysiology 12,13 . Epidemiological research has shown that the cancer incidence is higher in patients with HF than the general population even after controlling for other risk factors 14 . Given the impact on survival of newer pharmacological treatment for HF, it is of increasing clinical interest to identify strategies to reduce the burden of comorbid cancer in this population 12 .…”
Section: Introductionmentioning
confidence: 99%